DAMPAK PENGUMUMAN KEBIJAKAN BI 7 DAYS REPO RATE PADA SAHAM YANG TERDAFTAR DALAMJAKARTA ISLAMIC INDEX - Tisof Amri Izar Aminulloh; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This research aims to find out and explain Jakarta Islamic Index market reaction caused by BI 7 Days Repo Rate announcement by Bank Indonesia on April 15th , 2016. The approach used in this research is quantitative approach by using event study method which is the approach that is specialized to analyze a particular event that is believed to have an impact or reaction. Data used is secondary data including announcement data, stock price, trading volume during the period of observation and period of estimation. The object of the research is all the issuer that listed in Jakarta Islamic Index. Period of observation is 31 days started from 15 days before the event date to 15 days after the event date meanwhile the period of estimation is 55 days before period of observation. The focus of the research is to see the reaction shown by the change of Average Abnormal Return and Trading Volume Activity using one sample t-test and paired sample t-test. Data processing used a statistical tool of Stata version 14 by determining level of significance of 5%. The results of the research show that there is a significant average abnormal return around the date of announcement and there is a significant difference in trading volume activity before and after the right issue.Keywords: BI 7 Days Repo Rate, Sharia Stock, Event Study, Average Abnormal Return, Trading Volume ActivityREFERENCESAkhtar, dkk. 2017. Impact of interest rate surprises on Islamic and conventional stocks and bonds.Elsevier Ltd. Journal of International Money and Finance 79 (2017) 218–231Albaity, Mohamed. 2011. Impact of the Monetary Policy Instruments on Islamic Stock Market Index Return. Discussion Paper No. 2011-26| July 18, 2011.http://www.economics-ejournal.org/economics /discussio np a pers/2011-26Aliyah, Siti. 2016. Pengaruh Inflasi Dan Bi Rate Terhadap Indeks Harga Saham Jakarta Islamic Index (Jii) Tahun 2012 – 2014. Salatiga. Fakultas Ekonomi dan Bisnis Islam IAIN SalatigaBank Indonesia. 2017. Laporan Tahunan 2016:Mengoptimalkan Potensi, Memperkuat Reseliensi. Jakarta: Bank Indonesia (www.bi.gi.id) Burhanuddin. 2008. Pasar Modal Syariah (Tinjauan Hukum). Yogyakarta: UII PressCahyaningdyah dan Cahyasani. 2017. Analisis Reaksi Pasar Modal Atas Pengumuman Kenaikan Bi Rate Tanggal 12 November 2013. Semarang. Jurnal Maksipreneur, Vol. VI, No. 2, Juni 2017, hal. 56 – 65Dewan Syariah Nasional. 2004. Fatwa DVN No. 40/DSN-MUI/X/2003 tentang Pasar Modal dan Pedoman Umum Penerapan Prinsip Syariah di Bidang Pasar Modal (online) (http://www.dsnmui.or.id, diakses pada 2 Februari 2018)Fahmi, Irham. 2006. Analisis Investasi dalam Perspektif Ekonomi dan Politik. Bandung: PT Refika AditamaHalim, Abdul. 2015. Analisis Investasi dan Aplikasinya: Dalam Aset Keuangan dan Aset Riil. Jakarta: Salemba EmpatHaming dan Basamalah. 2010. Studi Keelayakan Investasi Proyek dan Bisnis. Jakarta: Bumi AksaraHartono, Jogiyanto. (2009). Teori Portofolio dan Analisis Investasi. Edisi Keenam. Yogyakarta: BPFE Universitas Gajah Mada.___________. 2015. Studi Peristiwa: Menguji Reaksi Pasar Modal Akibat Suatu Peristiwa. Yogyakarta: BPFE-YogyakartaHuda dan Nasution. 2007. Investasi Pada Pasar Modal Syariah. Jakarta: KencanaManan, Abdul. 2012. Hukum Ekonomi Syariah : Dalam Perspektif Kewenangan Peradilan Agama. Jakarta: Kencana Prenadamedia GroupSamsul, Mohammad. 2006. Pasar Modal dan Manajemen Portofolio. Jakarta: ErlanggaSharpe, William F. 1999. Investasi. Jakarta: PreanhallindoSorokina dan Thornton. 2016. Reactions of equity markets to recent financial reforms. Elsevier Inc. Journal of Economics and Business 87 (2015) 50–69Sutedi, Adrian. 2011. Pasar Modal Syariah: Sarana Investasi Keuangan Berdasarkan Prinsip Syariah. Jakarta: Sinar GrafikaTandelilin, Eduardus. (2010). Analisis Investasi dan Manajemen Protofolio.Yogyakarta: BPFE Fakultas Ekonomi UGM.Ulfah, Rizkia. 2011. Pengaruh Variabel Makroekonomi Terhadap Penetapan Nisbah Bagi Hasil Deposito Mudharabah Perbankan Syariah Di Indonesia. Jakarta: Fakultas Syariah dan Hukum UIN Syarif HidayatullahWarjiyo dan Solikin. 2003. Kebijakan Moneter di Indonesia. Jakarta: Pusat Pendisikan Dan Studi Kebanksentralan (PPSK)Wirartha, I. 2006. Metodologi Penelitian Sosial Ekonomi. Yogyakarta: C.V Andi Offset.